2020
DOI: 10.3390/su12020667
|View full text |Cite
|
Sign up to set email alerts
|

Social Trust Formation and Credit Accessibility—Evidence from Rural Households in China

Abstract: Trust as a form of social capital plays an important role in improving the cooperation between agents, especially in credit lending activities. Trust building has attracted significant research interest, and gift giving has been shown to be one of its main drivers. Nonetheless, the mechanism of gift giving in the formation of trust networks and the channels through which gift giving and trust affect cooperation require further investigation. In this paper, we first separate social trust into community trust an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The results of this study are in line with (Zhang et al, 2020;Okello Candiya Bongomin et al, 2017;Sanrego & Antonio, 2015) that the values of Social Capital embedded in the group affect the behavior of the poor in paying off their debts. 5) The beneficiary group affects repayment capacity in the opposite direction.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study are in line with (Zhang et al, 2020;Okello Candiya Bongomin et al, 2017;Sanrego & Antonio, 2015) that the values of Social Capital embedded in the group affect the behavior of the poor in paying off their debts. 5) The beneficiary group affects repayment capacity in the opposite direction.…”
Section: Resultssupporting
confidence: 89%
“…Several studies show that trust is significantly and positively related to economic growth and vice versa; the government's success in realizing a better level of economic development can strengthen people's social trust. Zhang et al (2020) prove that trust as a form of social capital plays an important role in increasing cooperation between agents, especially in credit lending activities. The results show that gift-giving is especially helpful in establishing trust at the personal level rather than at the community level.…”
Section: Core Concepts In Social Capitalmentioning
confidence: 98%
See 1 more Smart Citation
“…Ref. [15] showed that gift giving is mainly used to build personal trust, which facilitates access to informal lending for risk-sharing purposes. Ref.…”
Section: Introductionmentioning
confidence: 99%